2017
DOI: 10.1111/jav.01460
|View full text |Cite
|
Sign up to set email alerts
|

Plumage colour and the expression of stress‐related genes in gull chicks

Abstract: In many bird populations, individuals show remarkable differences in feather colouration, which are often linked to individual differences in physiological traits, but the mechanisms maintaining this covariation are still unclear. Here, we investigate the variability of the melanic colouration in yellow‐legged gull Larus michahellis chicks. In this species, hatchlings show high variability in the number and colour intensity of black spots in their plumage. In gulls, last‐laid eggs receive less antioxidants but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 82 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…Beta-actin gene ( ACTB ) was used as reference gene 66 , and gene-specific primers were designed using sequence information obtained from previously published sequences for ACTB , KIT , CASP7 , and SIRT1 genes in the yellow-legged gull 67 or using the available sequences in Charadriiformes (see Supplementary Methods and Table S5). The level of expression was measured in a 20 µl reaction volume, and all reactions were performed in duplicate (see details in Supplementary Methods).…”
Section: Methodsmentioning
confidence: 99%
“…Beta-actin gene ( ACTB ) was used as reference gene 66 , and gene-specific primers were designed using sequence information obtained from previously published sequences for ACTB , KIT , CASP7 , and SIRT1 genes in the yellow-legged gull 67 or using the available sequences in Charadriiformes (see Supplementary Methods and Table S5). The level of expression was measured in a 20 µl reaction volume, and all reactions were performed in duplicate (see details in Supplementary Methods).…”
Section: Methodsmentioning
confidence: 99%
“…Another important feature of the plumage is the color of feathers, which can impact the ability of chickens to respond under HS conditions. A recent study demonstrated that dark chicks showed a lower expression rate of genes belonging to pathways of stress (cellular stress: SOD2 and HSPA8 ; DNA damage repair: ALKBH3 ) than paler chicks [ 74 ]. This happens because the plumage element reduced solar heat gain by 5% in both light and dark plumages.…”
Section: Phenotypes Against Hsmentioning
confidence: 99%
“…We do not intend to describe all dichromatisms in the birds of the Western Palearctic, but to test for the direction of the difference in the hues of visible wavelengths for melanin pigments in adult males and females. In this regard, we did not consider sexual dichromatisms in juvenal plumages, such as the one recently described for the yellow-legged gull Larus michahellis, in which male chicks have larger spotted areas and darker spots in the head than female chicks (Diaz-Real et al 2017). This sex-specific coloration is noticeable as the adult birds are monochromatic.…”
Section: Assessment Of Color Traitsmentioning
confidence: 99%